"Accidental, really?" Attributional bias in patients with Parkinson's disease. (February 2022) - Decombe, Léa; Henry, Audrey; Decombe, René; Tir, Mélissa; Doé de Maindreville, Anne; Galland Hairabedian, Lou; Kaladjian, Arthur; Raucher-Chéné, Delphine
Abstract: Introduction: Among the cognitive domains impaired in Parkinson's disease (PD), social cognition has received particular attention in recent years. Nevertheless, attributional bias, a social-cognitive subdomain, has not yet been studied in this population, despite its potential relationship with neuropsychiatric symptoms, and despite the possibility that deep-brain stimulation of the subthalamic nucleus, an effective treatment for disabling motor symptoms, worsens cognitive impairment. The present study therefore compared the attributional bias of patients with PD (stimulated and nonstimulated subgroups) with that of controls. It also explored the potential correlations between patients' attributional bias and their clinical scores. Methods: Thirty-two patients with PD (12 stimulated and 20 nonstimulated) were recruited and matched with 32 healthy controls. Attributional bias was assessed using the Ambiguous Intentions Hostility Questionnaire, which yields three subscores: Hostility Bias, Aggression Bias, and Blame. Depressive symptoms (Hamilton Rating Scale for Depression), paranoid thoughts (Paranoia Scale), global cognition (Montreal Cognitive Assessment), and social functioning (Social Functioning Questionnaire) were also assessed. Results: Patients exhibited more hostile and aggressive biases than controls, especially in ambiguous situations. Stimulated patients had greater hostility and aggression biases and a higher blame score than controls in accidental situations. No significant differences were observed between stimulated and nonstimulated patients. Conclusion: To our knowledge, this is the first study to have assessed attributional bias in patients with PD and explored the impact of deep-brain stimulation on this particular subdomain of social cognition. Results suggest that patients exhibit attributional bias, and this impairment may be exacerbated in stimulated patients. Highlights: Attributional bias is a cognitive bias in the domain of social cognition. Patients with Parkinson's disease (PD) present attributional bias. PD patients present hostile and aggressive biases, notably in ambiguous situations. No impact of deep brain stimulation was detected on attributional biais